International consensus on the use of genetics in the management of hereditary angioedema - Germenis, Anastasios; Kirschfink, Michael (The journal of allergy and clinical immunology. In practice, 2020)
Hereditary angioedema (HAE) is becoming much more genetically complex than was initially considered. Thus, the role of HAE genetics is expanding beyond research laboratories, and the genotyping of subjects suffering from HAE has become diagnostically indispensable in clinical practice. The synthesis and interpretation of the clinical and biochemical analyses to facilitate appropriate genetic test selection has thus also become significantly more complex. With this in mind, an international multidisciplinary group of 14 experts in HAE genetics and disease management was convened in October 2018. The objective was to develop clear, actionable, evidence- and consensus-based statements aiming to facilitate the communication between physicians treating patients with HAE and clinical geneticists, and thus promote the effective use of genetics in the management of the disease. Eleven consensus statements were generated, encompassing considerations regarding the clinical indications for genotyping patients with angioedema, the methods of detection of HAE-causative variants, the variant pathogenicity curation, the genotyping of patients with HAE in the clinic, and genetic counseling. These statements are intended both to guide clinicians and to serve as a framework for future educational and further genetic testing developments as the field continues to evolve rapidly.
Available online 24 October 2019
Gesehen am 23.06.2021